Using saturation phenomenon to improve energy harvesting in a portal frame platform with passive control by a pendulum - Rocha, Rodrigo Tumolin [UNESP]; Balthazar, Jose Manoel [UNESP]; Tusset, Angelo Marcelo; Piccirillo, Vinicius; Felix, Jorge Luis Palacios (Springer Nature, 2016)
A new model of energy harvester based on a simple portal frame structure subjected to saturation phenomenon is presented. Energy is collected via a piezoelectric device whose nonlinearities are considered in the mathematical model. The system is a bistable Duffing oscillator presenting chaotic behaviour. Optimization of power harvesting and stabilization of chaotic motions to a given periodic orbit is obtained analysing the average power output and bifurcation diagrams. Control sensitivity to parametric errors in the damping and stiffness parameters of the portal frame is studied. The proposed passive control technique uses a simple pendulum tuned to the vibrations of the structure to improve energy harvesting. The results show that with the implementation of this control strategy it is possible to eliminate the need for active of semi-active control, usually more complex. The control also provides a way to regulate the energy captured to a desired operating frequency.